ANALYSIS OF DEMAND FOR SELECTED AGROCHEMICAL INPUTS AMONG OIL PALM FARMERS IN EDO STATE, NIGERIA - Adeyemo, R; Oke, J T O; Ogunleye, A S; Kehinde, A D; Ewemade, B O (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2017)
Agrochemicals are important inorganic inputs in oil palm production to improve quantity and quality of its products. Thus, this paper investigated demand for the selected agrochemical among oil palm farmers in Edo state. Specifically, it described the socioeconomics characteristics of the farmers; analyzed the demand of agrochemicals among oil palm farmers; determined the factors affecting the demand for agrochemicals among oil palm farmers; and estimated the costs and returns to the use of agrochemical among the oil palm farmers. A multistage sampling procedure was used to obtain data from 100 respondents for the study. Data collected were analyzed using descriptive statistics, probit regression model, and budgetary analysis. The result showed average values of 46.49 10.6 years for age, 14.74±7.01 years for formal education, 7.25 4.92 persons for household size, and 7.43±6.58 hectares for farm size.  It further showed that 85%, 78%, 14% of the respondents demanded for herbicides, fertilizer, and pesticide, respectively. The mean quantities applied were 150 kg/hectare, 4.41 kg/hectare, and 3.53 kg/ hectares for fertilizer, herbicide, and pesticide respectively. Probit regression estimates revealed that factors such as unit cost of fertilizer (P<0.01), quantity of fertilizer applied (P<0.01), and cost of hired labour (P<0.1) were the significant  determinants of demand for fertilizer, while the age of the farmer (P<0.01), unit cost of herbicides (P<0.01), the size of farm applied (P<0.01), farming experience (P<0.1), the distance to the input market (P<0.01) and the quantity of herbicides(P<0.01) were the significant determinants of demand for herbicides in the study area. Budgetary analysis showed that average gross margin and rate of return were ₦580354.26 and N3.26, respectively. In accordance with the finding of the study, we therefore, recommend that a subsidized cost of agrochemicals as well as reduction in its transport cost would encourage farmers to demand for more agrochemical inputs thereby improving oil palm production in the study area.